2012
DOI: 10.1002/ajhb.22266
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of breast milk macronutrient composition in filipino mothers

Abstract: The relative lack of associations between maternal diet or body composition and milk composition at Cebu is consistent with past studies and suggests that milk composition may be buffered against fluctuations in maternal dietary intake or nutritional status. We speculate that the tendency for milk composition to vary between populations faced with different nutritional ecologies, but to show minimal responsiveness to intake during lactation, may enhance the reliability of milk composition as a stable intergene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
103
0
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(132 citation statements)
references
References 79 publications
(103 reference statements)
12
103
0
13
Order By: Relevance
“…energy, protein, NPN, lactose and fat content, are consistent with previous observations [22][23][24][25] . There was a great variability in the composition between mothers and during lactation.…”
Section: Human Milk Compositionsupporting
confidence: 81%
“…energy, protein, NPN, lactose and fat content, are consistent with previous observations [22][23][24][25] . There was a great variability in the composition between mothers and during lactation.…”
Section: Human Milk Compositionsupporting
confidence: 81%
“…23 Villalpando et al found a strong positive correlation between body fat mass and fat content of breast milk, 20 in aggreement with research by Barbosa et al 21 Conversely, no significant correlation was found between fat content of milk and maternal body fat mass (P=0.743), total body fluid (P=0.442), or muscle mass (P=0.853). Similarly, Quinn et al 22 found that body composition, in this case the fat mass, was not a predictor of the fat content of milk. This result may be related to the possibility that adequate food intake was the main source of milk fat, so body composition had little effect.…”
Section: Discussionmentioning
confidence: 99%
“…19 Studies on maternal body fat mass have also been inconclusive. Body fat mass was positively correlated with fat content in breast milk in studies by Villalpando et al 20 and Barbosa et al, 21 but Quinn et al 22 reported that body fat mass was not a predictor of breast milk fat content. The aim of the study was to investigate breast milk fat content of Indonesian mothers at 1 month after delivery and to assess for possible correlations between breast milk fat content and either maternal body composition or nutritional intake.…”
mentioning
confidence: 91%
“…The physiological processes by which mammary glands synthesize breast milk necessarily reflect, in part, maternal characteristics at the time of lactation, or even in the months, and years before lactation (Hinde and Milligan, 2011;Quinn et al, 2012). For these reasons, milk can vary between populations, across lactation, among women within populations, and even within mother during a single nursing bout and throughout the day.…”
Section: Sources Of Variation In Human Milkmentioning
confidence: 99%
“…Researchers have only begun to define normal milk variation across populations and how it influences the postnatal period and beyond (Neville et al, 2012). Many of the emerging questions in human biology are linked to lactation, from unique aspects of primate Milligan and Bazinet, 2008) and human life histories (Fujita et al, 2011), parental investment (Fujita et al, 2012;Hinde, 2009;Powe et al, 2010), and developmental programming (de Moura et al, 2008;Hinde and Capitano, 2010;Miralles et al, 2006;Newburg et al, 2010;Palou et al, 2009;Pico et al, 2007;Prentice, 2005;Quinn, 2011;Quinn et al, 2012;Savino et al, 2009;Stocker and Cawthorne, 2008;Weyerman et al, 2007). In addition, lactation is implicated in human evolutionary biology, including the evolution of large brains and body fat (Kuzawa, 1998;Martin, 1981), childhood (Bogin, 1999;Konner, 2010;Sellen, 2007), reproductive timing (Al-Sahab et al, 2011) and the developmental origins of adult metabolism (Kuzawa and Quinn, 2009;Wells, 2003).…”
Section: Introductionmentioning
confidence: 99%